(untitled) (Economic and Political Thought, 2018)
The article aims to assess the differences in the level of remuneration and identify factors that influence this differentiation in the Kuyavian-Pomeranian Voivodeship in the period of 2007–2016. The analysis covers the differences in remuneration in different occupational groups. The average gross monthly remuneration in the voidodeship, standard deviations in the region and the relation between the average remuneration and the dynamics of increase are used. Based on the data, statistical data such as the average, standard deviations and the variation index are calculated. Statistical data published in the 2007–2016 Statistical Yearbooks of the Statistical Office in Bydgoszcz are used for the analysis and assessment.